2013
DOI: 10.1002/jnr.23322
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Mechanisms and effects of curcumin on spatial learning and memory improvement in APPswe/PS1dE9 mice

Abstract: Evidence suggests that curcumin, the phytochemical agent in the spice turmeric, might be a potential therapy for Alzheimer's disease (AD). Its antioxidant, anti-inflammatory properties have been investigated extensively. Studies have also shown that curcumin can reduce amyloid pathology in AD. The underlying mechanism, however, is complex and is still being explored. In this study, we used the APPswe/PS1dE9 double transgenic mice, an AD model, to investigate the effects and mechanisms of curcumin in the preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 54 publications
0
65
0
Order By: Relevance
“…29 We have previously reported that curcumin improves the spatial learning and memory abilities of APPswe/ PS1dE9 double transgenic mice. 23 Therefore, we sought to determine whether curcumin affects the pathology of AD via the synapses. Specifically, we sought to determine whether curcumin influences the structures and functions of the synapses of APPswe/PS1dE9 double transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 We have previously reported that curcumin improves the spatial learning and memory abilities of APPswe/ PS1dE9 double transgenic mice. 23 Therefore, we sought to determine whether curcumin affects the pathology of AD via the synapses. Specifically, we sought to determine whether curcumin influences the structures and functions of the synapses of APPswe/PS1dE9 double transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…The following doses were used in the curcumin treatment groups: the low-dose curcumin group (LDC) received 100 mg/kg/day, the medium-dose curcumin group (MDC) received 200 mg/kg/day, and the high-dose curcumin group (HDC) received 400 mg/kg/day. 23 …”
Section: Animalsmentioning
confidence: 99%
“…Then, we placed the cryovials into liquid nitrogen to freeze them and subsequently stored them at −80°C until the tissues were used for a western blot analysis. 9 …”
Section: Tissue Preparationmentioning
confidence: 99%
“…12 The CA1 region of the hippocampus is the core functional area of learning and memory; therefore, we chose this region of the APPswe/PS1dE9 double transgenic mice as the research object. 13 9 The experiments were strictly performed abiding by the regulations and the guidelines of Beijing for the use of animals in research, and we received permission from the Animal Research Ethics Board of Dongzhimen Hospital. The mice were kept in a temperature-controlled environment with 12 h of light and 12 h of dark.…”
Section: Introductionmentioning
confidence: 99%
“…In a 4 weeks randomized, double-blind, placebo-controlled human trial, curcumin (400 mg) has been shown to significantly improve working memory and mood after treatment [35]. In animal studies of curcumin in APPswe/PS1dE9 double transgenic AD mice also showed improved spatial learning and memory ability [36,37]. Such effects may conducted through reducing Aβ40, Aβ42, and aggregation of Aβ-derived diffusible ligands in the mouse hippocampal CA1 area, increase the expression of synapse-related proteins PSD95 and Shank1 and improve structure and plasticity of synapse.…”
mentioning
confidence: 99%